SDSS-IV MaNGA: uncovering the angular momentum content of central and satellite early-type galaxies - Greene, J.E.; Leauthaud, Alexie; Emsellem, Eric; Ge, J.; Aragón-Salamanca, Alfonso; Greco, J.; Lin, Y.-T.; Mao, S.; Masters, K.; Merrifield, M.; More, S.; Okabe, N.; et al. (American Astronomical Society, 2018)
We study 379 central and 159 satellite early-type galaxies with two-dimensional kinematics from the integral field survey Mapping Nearby Galaxies at APO (MaNGA) to determine how their angular momentum content depends on stellar and halo mass. Using the Yang et al. (2007) group catalog, we identify central and satellite galaxies in groups with halo masses in the range 1012:5 h-1 M_ < M200b < 1015 h-1 M_. As in previous work, we see a sharp dependence on stellar mass, in the sense that ~70% of galaxies with stellar mass M_ > 1011 h-2 M_ tend to have very little rotation, while nearly all galaxies at lower mass show some net rotation. The ~ 30% of high-mass galaxies that have significant rotation do not stand out in other galaxy properties except for a higher incidence of ionized gas emission. Our data are consistent with recent simulation results suggesting that major merging and gas accretion have more impact on the rotational support of lower-mass galaxies. When carefully matching the stellar mass distributions, we find no residual differences in angular momentum content between satellite and central galaxies at the 20% level. Similarly, at fixed mass, galaxies have consistent rotation properties across a wide range of halo mass. However, we find that errors in classification of centrals and satellites with group finders systematically lowers differences between satellite and central galaxies at a level that is comparable to current measurement uncertainties. To improve constraints, the impact of group finding methods will have to be forward modeled via mock catalogs.